Motivational traits: An objective behavioral test using a computer game - Fernández-Avilés, Daniel; de Antonio, Angélica; Villalba-Mora, Elena (Frontiers in Psychology, 2022)
An objective behavioral test for motivational traits has been developed taking as a reference the structure of the Motivational Trait Questionnaire, which is a validated self-report questionnaire to measure motivational traits in the population. The objective test consists of a computer game, which makes it possible to evaluate a person’s motivational traits and to display them on the same scale as the Motivational Trait Questionnaire. To evaluate the validity of the results obtained in the measurement of motivational traits using the objective behavioral test, a study was carried out with 31 participants whose motivational traits were evaluated using the two methods, and the results obtained were compared to find out whether the two forms of assessment can be considered equivalent. Statistical tests support the high degree of similarity of the results, concluding that the objective behavioral test can be a useful instrument to assess motivational traits as an alternative to the self-report questionnaire. Despite the increasing popularity of game-based assessment of personality traits, this is the first time a game has been designed for the assessment of motivational traits. Being able to obtain a model of the user’s motivational traits without having to rely on a questionnaire opens the possibility to build software applications that adapt to the user’s motivational profile, providing them with the kind of motivational support that best fits their needs.